If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(7m + 7) = -27 + 5m Reorder the terms: 3(7 + 7m) = -27 + 5m (7 * 3 + 7m * 3) = -27 + 5m (21 + 21m) = -27 + 5m Solving 21 + 21m = -27 + 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. 21 + 21m + -5m = -27 + 5m + -5m Combine like terms: 21m + -5m = 16m 21 + 16m = -27 + 5m + -5m Combine like terms: 5m + -5m = 0 21 + 16m = -27 + 0 21 + 16m = -27 Add '-21' to each side of the equation. 21 + -21 + 16m = -27 + -21 Combine like terms: 21 + -21 = 0 0 + 16m = -27 + -21 16m = -27 + -21 Combine like terms: -27 + -21 = -48 16m = -48 Divide each side by '16'. m = -3 Simplifying m = -3
| 7x^3+16x^2-15x=0 | | 4(x+7)=-5x+19 | | 2k-k-1=9 | | -39-8x=4-3(1+6x) | | 1/2(4+6)-5= | | 14x-4+12x=1+16x | | 4(r+1)-4=7r+24 | | 4x^2+28x+49= | | -2p-5(2-2p)=6(p-4)-18 | | 5x+8x-16=6x+x | | (8x+3)(2x^2-9x-5)=0 | | 3w+9-8w=-31 | | x(x+1)-4(x+1)= | | 2(4v+7)=62 | | 2(x-7)=7 | | 4x^2y^4-12x^3y^2-8xy^3=0 | | 2x+4y-7x-7y=5 | | (x-9)(x-2)=0 | | -3w+7=-9w+49 | | 5+i^2-10(5+i)+26=0 | | 10x+17x-8+2=-8x+2-8 | | 10x+17x-8+2= | | x(3-y)+y(x+6)= | | 2y+5=4y+13 | | 24-3x=4+2x | | (6t-7)=2(t+1)+2 | | 2A-ha=hb | | 3(5z-1)-4(z+9)=2(2+1) | | 2-2z=14 | | 50x^2=0.02 | | 4x-15=-18+7x | | 3s-24=-24+4s |